12012 fundamental mechanisms behind nanotechnology applications in oil and gas: Emerging nano-EOR processes - Wang, Ningyu; Zhao, Yuzhou; Prodanović, Maša; Balhoff, Matthew T.; Huh, Chun (Frontiers in Nanotechnology, 2022)
As the important role of enhanced oil recovery (EOR) in meeting the world’s energy requirement is growing, use of nanoparticles in lieu of, or in combination with, the existing EOR agents to expand EOR’s applicable range is receiving significant attention. Two of the most actively investigated applications are: (1) wettability alteration by addition of nanoparticles into the waterflood injection water, and (2) use of nanoparticle-stabilized Pickering foams and emulsions mainly for EOR process mobility control. As comprehensive reviews are recently available on these topics, two other emerging nanoparticle applications are critically reviewed here: (1) nanoparticle addition for enhanced polymer flooding, and (2) use of magnetic nanoparticles for oil displacement control. Three and five proposed mechanisms of these two applications are critically reviewed, respectively. The most recent progresses are covered, and the challenges and possible future works are discussed.